2019
DOI: 10.5935/1518-0557.20190028
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with spontaneous abortion following intracytoplasmic sperm injection (ICSI)

Abstract: Objective: The aim of this study was to describe the miscarriage rates and the factors associated with cases of spontaneous abortion observed in women offered intracytoplasmic sperm injection (ICSI). Methods: This cross-sectional study enrolled women who became pregnant with the aid of ICSI treated at the Babol Infertility Center (Iran) within a period of five years (2010-2015). Data were collected from patient charts and, in some cases, through phone calls. The study l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(27 reference statements)
0
5
0
2
Order By: Relevance
“…Pre-pregnancy BMI is an important indicator of pregnancy outcomes (12,13). Nevertheless, studies on the associations between pre-pregnancy BMI and miscarriages are limited, and the conclusions are inconsistent for pregnant women receiving ART treatment (14)(15)(16)(17)(18). Although some studies have reported that pre-pregnancy underweight and obesity both increase the miscarriage rate of pregnant women receiving ART treatment (19,20), other studies have reported no adverse effects of prepregnancy underweight, overweight, or obesity on the miscarriage rate of ART (14,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-pregnancy BMI is an important indicator of pregnancy outcomes (12,13). Nevertheless, studies on the associations between pre-pregnancy BMI and miscarriages are limited, and the conclusions are inconsistent for pregnant women receiving ART treatment (14)(15)(16)(17)(18). Although some studies have reported that pre-pregnancy underweight and obesity both increase the miscarriage rate of pregnant women receiving ART treatment (19,20), other studies have reported no adverse effects of prepregnancy underweight, overweight, or obesity on the miscarriage rate of ART (14,18).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies on the associations between pre-pregnancy BMI and miscarriages are limited, and the conclusions are inconsistent for pregnant women receiving ART treatment ( 14 18 ). Although some studies have reported that pre-pregnancy underweight and obesity both increase the miscarriage rate of pregnant women receiving ART treatment ( 19 , 20 ), other studies have reported no adverse effects of pre-pregnancy underweight, overweight, or obesity on the miscarriage rate of ART ( 14 , 18 ). Thus, the objective of the present study was to analyze the influence of pre-pregnancy BMI on miscarriage in women receiving ART treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The older the male, the higher the reproductive cell mutation rate of the offspring. Various factors associated with increasing age will destroy the DNA replication and repair mechanism and increase the possibility of DNA breakage, thus leading to the occurrence of abortion 29 , 30 . Although a consensus has been reached on the age of advanced mothers, which is agreed to be 35 years old, there is currently no agreement on the definition of the age of elderly fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Total fertilization failure (TFF) occurs in 1–5% of ICSI cases ( Kyono et al , 2012 ; Montag et al , 2012 ; Vanden Meerschaut et al , 2014b ; Kashir et al , 2018 ; Basirat et al , 2019 ; Bassiri et al , 2020 ). Moreover, associations have been identified between embryo grading and congenital malformations, endocrine profile changes and deficient hearing in ICSI-conceived babies ( Abel et al , 2019 ; Belva et al , 2019 ; Yasemin Sert et al , 2019), while age, antimullerian hormone levels and antral follicle counts are associated with live birth rates following ICSI, with other hormones currently under investigation ( Metello et al , 2019 ; Zheng et al , 2019 ; Song et al , 2020 ; Tarín et al , 2020 ; Tiegs et al , 2020 ; Wang et al , 2020 ; Ye et al , 2020 ; Zanetti et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%